2020
DOI: 10.1098/rsos.191482
|View full text |Cite
|
Sign up to set email alerts
|

An experimental approach to evaluate the potential of drones in terrestrial mammal research: a gregarious ungulate as a study model

Abstract: Research on the use of unmanned aircraft systems (UAS) in wildlife has made remarkable progress recently. Few studies to date have experimentally evaluated the effect of UAS on animals and have usually focused primarily on aquatic fauna. In terrestrial open arid ecosystems, with relatively good visibility to detect animals but little environmental noise, there should be a trade-off between flying the UAS at high height above ground level (AGL) to limit the disturbance of animals and flying low enough to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 35 publications
0
40
2
Order By: Relevance
“…This action may occur in wild populations that have been exposed to human presence for a long time, for example, by human tourism activities around their habitat [23]. However, our study shows that the behavioral changes that occur are not that significant, compared to studies conducted on guanacos [24]. This research suspects that the size of the type of UAV used provides a different level of interference.…”
Section: Animal Reaction To the Passage Of The Uavcontrasting
confidence: 62%
“…This action may occur in wild populations that have been exposed to human presence for a long time, for example, by human tourism activities around their habitat [23]. However, our study shows that the behavioral changes that occur are not that significant, compared to studies conducted on guanacos [24]. This research suspects that the size of the type of UAV used provides a different level of interference.…”
Section: Animal Reaction To the Passage Of The Uavcontrasting
confidence: 62%
“…The author found that drones with a flying altitude of < 50 m HAGL were good for detecting and recognizing animals. However, flying at lower altitudes takes longer flight time to survey the same area and increases the risk of disturbing the animals [1]. Increasing detection by lowering the drone's height certainly has implications for increasing the sound emitted by drone engines.…”
Section: Animal Detectability and Parametersmentioning
confidence: 99%
“…drones) are capable of moving fast, scanning forests from top to bottom and are very promising for expanding the scale of canopy surveys that are very useful in studying wildlife ecology. Drone imagery has proven useful for wildlife surveys in open areas, for example, guanaco [1], Artic birds [2], kangaroo [3], caribou [4], waterfowl [5], hippos [6], and crocodile [7]. Meanwhile, for animals living in tree canopies, UAVs are not widely used because of the difficulty of visually detecting these animals with standard aerial imagery.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies enable more wide ranging and accurate data collection in societies with hundreds of individuals (Charpentier et al, 2021; Inoue et al, 2019; Schroeder et al, 2020). For instance, our use of drones succeed in obtaining positional and behavioural data of more than a hundred of feral horses in Portugal, which formed multilevel society with a two-layered structure with units—a group of individuals which stayed closer than 11.5m more than 70% of the time—and a herd—an aggregation of units (Maeda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%